The efficacy of a self‐managed Acceptance and Commitment Therapy intervention DVD for physical activity initiation. (3rd April 2014) - Moffitt, Robyn; Mohr, Philip
<x xml:space="preserve">Abstract</x> Objectives Initiating and maintaining physical activity presents the individual with challenges of inconvenience, discomfort, and counteractive energy. Addressing these challenges requires an intervention that elicits motivation to engage in this activity, minimizes the direct relationship between unwanted internal experiences and inaction, and is also in itself accessible and convenient. Accordingly, this study investigated the efficacy of a self‐managed Acceptance and Commitment Therapy (ACT) intervention delivered via DVD and tailored for physical activity initiation. Design and methods Fifty‐nine minimally active community participants were randomly allocated to receive a 12‐week pedometer‐based walking programme, or the same walking programme with the additional provision of the ACT DVD. The primary outcome was overall physical activity level (assessed at baseline and post‐intervention), and the secondary outcome was pedometer‐assessed step count (measured at 4‐weekly intervals throughout the intervention period). Results Participants who received the ACT DVD achieved a significantly greater increase in physical activity levels post‐intervention, were more likely to achieve the goals specified in the programme, and reported a higher average step count than participants who received the walking programme in isolation. Conclusions The ACT intervention, delivered via DVD for the promotion of physical activity, proved a simple, efficient, and accessible method to encourage positive short‐term increases in an important health‐promoting behaviour. <boxed-text content-type="box" id="bjhp12098-blkfxd-0001" position="anchor" orientation="portrait"> Statement of contribution What is already known? ACT interventions can increase physical activity levels through augmenting initiatory self‐regulatory control. Face‐to‐face delivery presents challenges of accessibility and feasibility for community implementation. There is a need for effective interventions that maximize impact while minimizing inconvenience. What does this study add? Supplementing a walking programme with a self‐managed ACT DVD produced significant increases in physical activity. The ACT DVD is a convenient, accessible, and potentially cost‐effective approach to physical activity initiation. ACT lends itself to implementation as a self‐managed electronically delivered intervention. </boxed-text>